Incidence of neoplastic diseases in infants in Cienfuegos province from January 1988 to December 1998. - Luis Pedro Hernández Sosa; Sonia Pérez García; Mileny Acosta Fonseca (Medisur)
Background: The study of neoplasias in children gathers of cancer that appear in children less than 15 years of age although some authors have stated that this age should be widened till youngsters less than 20 years. Although neoplasias in this age group only represent around 5 % of all neoplasms, there are important reasons that justify their investigation. Objective: To analyse the epidemiological characteristics of neoplasm in children in Cienfuegos province. Method: Descriptive- retrospective study with a universe that gathered all the patients less than 15 years of age who had a diagnosis of neoplasia in Cienfuegos province, Cuba in the period January1988 – December 1998 . The rate of incidence per 100 000 inhabitants aged less than 15 was obtained and the variables under study were identification data: age, sex, race, (classified as whites and no whites ), municipality of origin and type of tumour. The difference in incidence at the beginning and at the end of the period under study were calculated too. Results: The Annual means in the province was 12.45 x 10 5 inhabitants. The most affected age group was from 1 to 4 years of age with a rate of incidence of 15,25 x 10 5 inhabitants, with a predominance of white females. Cruces was the most affected municipality with a rate of 22,26 x 10 5 inhabitants. The tendency of infantile cancer in the province has diminished and it is more significant in acute lymphoblastic leukemia.